Fruit colour and edge effects poorly explains frugivorous bird-plant interactions in disturbed semideciduous forests (Acta Scientiarum. Biological Sciences, 2018)
Fruit colour is considered an important feature mediating interactions between plants and frugivorous birds. Despite that, colour mediated interactions are context-dependent, and habitat disturbances may affect how frugivorous birds perceive fruit colours. This study assessed the influence of fruit colour and edge effect on the consumption of artificial fruits by frugivorous birds in three disturbed semideciduous forests in southeastern Brazil. In each of those areas, we performed a field experiment in which we placed artificial fruits of three different colours on plants and recorded their consumption by birds. Red-coloured fruits were ingested more often than yellow, but neither of them was consumed differently from dark-blue. Edge effect only affected consumption of yellow fruits. Our data neither support the hypothesis of preferential consumption of the highest contrasting colours nor of increased fruit consumption in the forest interior. These findings indicate that colour and edge effects, as well as the interaction between them, may not be strong predictors of fruit choice by birds in disturbed environments, especially because generalist species, which are less sensitive to the physical alterations in forests, are favoured in these areas.